ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ ДИНАМІЧНОГО КЕРУВАННЯ РЕЖИМАМИ РОЗПОДІЛЬНИХ МЕРЕЖ - Жаркін, А.Ф.; Попов, В.А.; Ярмолюк, О.С.; Палачов, С.О.; Наталич, В.О. (Інститут електродинаміки Національної академії наук України, 2025)
The intensive spread use of not dispatchable renewable energy sources, which are integrated into distribution systems, can create significant problems with ensuring the efficiency and even technical admissibility of their operating modes. The difficulties that arise cannot be eliminated by using existing control methods, which are not able to rationally and adequately respond to changes in the modes of operation caused by the unstable, with difficult-to-predict outputs of local energy sources. In this regard, the article considers the feasibility of using remotely controlled switching devices, which should provide the opportunity to quickly change the topology, and, accordingly, the load flow in certain circuits of distribution networks. The issues of determining the best locations for the remotely controlled switches and the algorithm for their operation, taking into account the limited switching resource and the actual uncertainty of information, are consistently resolved. The feasibility and possibility of involving the factor of reliability of power supply for making more justified decisions regarding the change of the distribution network mode are demonstrated. The results obtained are aimed to reduce of electrical energy losses, taking into account the reliability and efficient use of the switching resource of remotely controlled switches, which thereby allows expanding the implementation of renewable energy sources.Ref. 10, fig. 3, table.